Detecting Ships in the New Zealand Exclusive Economic Zone: Requirements for a Dedicated SmallSat SAR Mission - Krecke, Jan; Villano, Michelangelo; Ustalli, Nertjana; Austin, Andrew C. M.; Cater, John E.; Krieger, Gerhard (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing, 2021)
The performance tradeoffs of a smallsat synthetic aperture radar (SAR) system for maritime surveillance in the coastal waters of New Zealand are investigated. The lower costs of smallsat platforms allow for a constellation of SAR satellites that can be launched from New Zealand using an existing local launch service provider. The minimum SAR image quality necessary for a smallsat system to achieve a desired detection performance is determined using existing X-band satellite data. The image quality is specified in terms of noise-equivalent sigma zero (NESZ) and resolution. It was found that for a resolution cell of 4 m2 a system NESZ of-1.7 dB is sufficient to detect small fishing vessels with a probability of detection of 0.5, while maintaining the probability of false alarm below 10-10. These requirements are translated into a preliminary SAR system design.
Created from Fastlane, Scopus look-up
Keywords: detectors; low earth orbit satellites; marine vehicles; radar clutter; radar remote sensing; satellite antennas; sea surface; spaceborne radar; Synthetic aperture radar